MEMBER PERCEPTIONS ON BUSINESS CAPITAL FINANCING PRODUCTS IN EMPOWERING MICRO, SMALL AND MEDIUM ENTERPRISES AT BAITUL MAAL WAT TAMWIL "UMMAT SEJAHTERA ABADI" NALUMSARI BRANCH - Dewi Laras; Supardi Supardi; Yunus Mustaqim (JURNAL PROFIT, 2025)
The financial system in Indonesia continues to progress, especially in financial institutions based on Sharia. Sharia Microfinance Institutions actors develop along with an increase in turnover which is influenced by member perceptions of a product. The product that is often used by MSME players is a business capital financing product that can assist in capital. However, some people still cooperate with conventional financial institutions that have elements of ribawi which are prohibited by Islam in the Al-Qur'an and As-Sunnah because they are considered detrimental to one party. Therefore, the presence of BMT is needed because it can be an alternative solution for business people who need additional capital without worrying about usury. This study aims to describe the perception of members on business capital financing products in empowering MSMEs at BMT Ummat Sejahtera Abadi Nalumsari Branch. This study applies a type of field research with a qualitative approach and descriptive method. The data obtained in this study is in accordance with the facts that occurred at BMT Ummat Sejahtera Abadi Nalumsari Branch obtained through observation, interviews with branch heads, marketing employees and 5 members on business capital financing products and documentation. Data analysis is done by reducing data, presenting data and verification and conclusions. Member perceptions related to business capital financing products available at BMT Ummat Sejahtera Abadi Nalumsari Branch obtained good results, evidenced by an increase in the number of members by 1,34% and progress on the business being carried out. This perception is influenced by the quality of service and the price of a product that can be calculated because the margin or service provided tends to be low.